2005
DOI: 10.1007/s00125-005-1776-5
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of coeliac disease in adult Danish patients with type 1 diabetes with and without nephropathy

Abstract: To the Editor: Coeliac disease causes malabsorption due to small bowel villous atrophy, which normalises when gluten, which is found in wheat, rye and barley, is withdrawn from the diet. Coeliac patients should be treated with a gluten-free diet that corrects the intestinal malabsorption and protects against the development of osteoporosis and intestinal lymphoma.As shown in several studies (review [1]), type 1 diabetes is associated with a high prevalence (2-10%) of coeliac disease. This has, in part, been ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 7 publications
0
18
0
1
Order By: Relevance
“…A study of 967 people with type 1 diabetes, of which 462 had nephropathy, found no difference in the prevalence of CD (15). A study of children with type 1 diabetes and established CD on a GFD was compared with a control group with diabetes alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of 967 people with type 1 diabetes, of which 462 had nephropathy, found no difference in the prevalence of CD (15). A study of children with type 1 diabetes and established CD on a GFD was compared with a control group with diabetes alone.…”
Section: Discussionmentioning
confidence: 99%
“…Two previous studies have examined the effect of CD on diabetic nephropathy but were conflicting (15,16). There are currently no studies examining the prevalence of retinopathy in individuals with both type 1 diabetes and CD.…”
mentioning
confidence: 99%
“…55 Interestingly, an enhanced cesarean delivery rate was also described for type 1 diabetes, an autoimmune condition that has immunologic overlap with celiac disease. [56][57][58] Moreover, a moderately enhanced cesarean delivery rate has been described in mothers with both celiac disease and IBD. 59,60 Given the strong genetic factor in the pathogenesis of both diseases, the enhanced cesarean delivery rate might have contributed to an association between cesarean delivery and celiac disease; however, information on the family history was not obtained and genetic testing of patients and control subjects was not performed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In any case, the final result is the destruction of beta cells and progressive impairment of the blood glucose metabolism [82]. Some patients with type 1 diabetes may show a higher susceptibility to other conditions such as thyroiditis, Graves disease, Adisson disease, celiac disease, myasthenia gravis or to degenerative skin conditions such as vitíligo [83][84][85].…”
Section: Induced Pluripotent Stem Cells In the Treatment Of Diabetes mentioning
confidence: 99%